Understanding Character Education and Islamic Values in Early Childhood: A Phenomenological Analysis of Educators' Perspectives and Practices - Nafsaka Sajidin, Zayin (Sekolah Tinggi Agama Islam Kuningan, 2024)
Backround: Islamic character education is increasingly recognized for integrating moral and spiritual development with cognitive growth in early childhood settings, with direct implications for curriculum design and teacher training policies. This study examines how 42 educators in Malaysia, Indonesia, and the UAE implement Islamic character education and navigate related challenges.Objective: The study aims to understand how educators integrate Islamic character education, the challenges they face, and its impact on children's development.Method: Data were collected through in-depth semi-structured interviews, focus group discussions, and reflective journals over an 11-month period. Van Manen’s hermeneutic phenomenological approach was used for analysis.Findings and Implications: The study identified four key themes: (1) navigating between traditional and contemporary practices, (2) effective pedagogical strategies such as storytelling and role modeling, (3) challenges like resource limitations and balancing secular curricula, and (4) positive impacts on moral awareness, empathy, self-regulation, and religious identity.Conclusion: The study highlights the importance of integrating Islamic values in early childhood education through developmentally appropriate practices. It recommends culturally responsive professional development, authentic curriculum creation, and stronger parent-teacher collaboration to enhance the effectiveness of Islamic character education in early childhood settings.